Enhancement of supercapacitor efficiency by Fe3+ doping in hydrothermally synthesized NiO nanoparticles - Upadhyay L.; Dhanapandian S.; Suthakaran S.; Yadav B.; Kar K.K.; Kumar D. (My University, 2025)
This study examines the physicochemical and electrochemical characteristics of hydrothermally produced, 800°C-annealed pure and Fe3+ doped (0.02, 0.04, and 0.06 M) NiO nanoparticles(NPs).The face-centred cubic structure of NiO NPs was verified by XRD analysis, and doping resulted in a decrease in crystallite size from 43.92 nm to 19.67 nm.FE-SEM revealed dense and irregularly arranged granular morphologies, while EDAX confirmed successful Fe3+ incorporation into NiO matrix. UV–Vis DRS showed an increase in bandgap energy from 3.15 eV to 3.71 eV. XPS confirmed the presence of Ni2+ and Fe3+ with their elemental compositions. According to BET analysis, Fe3+ doping increases pore size and specific surface area, which raises specific capacitance.VSM analysis of pure and Fe3+ doped NiO NPs demonstrated a transition from a weak ferromagnetic to a distinctive ferromagnetic behaviour, which is beneficial for energy storage as well as data storage applications.The electrochemical studies showed that 0.06 M Fe3+ doped NiO had the maximum specific capacitance of 360.96 F g−1 at the scan rate of 10 mV s−1and EIS Nyquist plots showed enhanced electrical conductivity. These results highlight the possibility of Fe3+ doped NiO NPs as excellent electrode materials for high-efficiency supercapacitors. © 2024 Elsevier B.V.